The Flaws in the New Spelling Rules - Қ.А. Қыдырбaев (Journal of Oriental Studies, 2019)
On December 6, 2018, the new spelling rules of the Kazakh language alphabet based on the Latin alphabet, which was repeatedly reviewed, was published in the 11th issue of the newspaper “Egemen Qazaqstan” in the republican edition. The proposed spelling rules were developed and approved by the A.Baitursynov Institute of Linguistics and National Scientific and Practical Center Sh. Shayakhmetov in conjunction with the National Commission for the Transfer of the Kazakh Alphabet to Latin Graphics and it was carefully surveyed by conducting questionnaires among students of Higher Education Institutions of the Republic, pupils of secondary schools, as well as teachers-philologists and adults from some regions of the country before it was approved. The Spelling Rules project has been reviewed by independent experts and linguists from the University. However, when we examined the correct spelling rules, some of the disadvantages were observed. In this article, we will make our comments and suggestions to compile some of the shortcomings in some paragraphs by making comparisons, comparative analysis. Key words: Kazakh language, the Latin alphabet, spelling rules, loan words.